A microscopic survey of the human temporomandibular joint disc - Minarelli, A. M.; Liberti, E. A. (Blackwell Science, 1997)
The articular disc of the temporomandibular joint was studied in a foetuses and children group (GI), a dentate group of adults (GII) and an edentulous, elderly group of humans (GIII) by light microscopy. The main, constituent bundles of type I collagen fibres are stratified and are orientated sagittally, transversely and obliquely in the middle portion of the disc. In the thick, posterior portion, transverse bundles constitute the main feature. In the anterior portion of the disc, the fibres are sagittally and obliquely orientated. Type III. collagen fibres, intermingled with type I collagen fibres are present in all groups. The disc is cellular in nature in foetuses and children becoming more fibrous with age. Chondroid cells are observed in all portions of the discs in groups GII and GIII. Elastic fibres are numerous in GI discs and decrease in number in the disc with age. These fibres lie parallel to the collagen fibres in all three portions of the three groups.